Support workers’ experiences of work stress in long-term care settings: a qualitative study - Karol J. Czuba; Nicola M. Kayes; Kathryn M. McPherson (International Journal of Qualitative Studies on Health & Well-Being, 2019)
Background: Support-workers’ performance and well-being are challenged by increasingly high workloads and poor working conditions, leading to high levels of occupational stress. Aims: To explore the experiences of work stress for support-workers in New Zealand residential facilities. Design: An Interpretive Descriptive study. Methods: Data from ten (n = 10) support-workers were collected between December 2013 and June 2014, using semi-structured in-depth face-to-face interviews. Thematic analysis was used to identify key themes that captured participant reports of their experiences. Results: Work stress was conceptualized by participants as being an everyday experience of having too much to deal with and feeling under constant pressure. It appeared to be a complex and fluid experience representing an inherent, dynamic tension between reasons to be a caregiver and the burden of caregiving. Participants highlighted a range of influencing factors (including lack of recognition, person and work context, and coping strategies), which may account for that fluidity. Conclusion: The findings extend current knowledge about support-workers’ work stress by identifying the challenges relating to the lack of recognition of their role and expertize, the unintended consequences of person-centered care and the challenges faced by migrant support-workers.